2022
DOI: 10.3389/fenvs.2022.930728
|View full text |Cite
|
Sign up to set email alerts
|

Do Urbanization, Remittances, and Globalization Matter for Energy Consumption in Belt and Road Countries: Evidence From Renewable and Non-Renewable Energy Consumption

Abstract: Energy–growth nexus has gained immense interest among researchers, policymakers, and academicians, and with conclusive evidence, it is revealed that sustainable economic growth significantly relies on energy availability and security. Another line of studies postulated that excessive fossil fuel application had created adversity for environmental degradation and ecological imbalance. However, the energy demand from renewable and non-renewable has intensified with the act of several macro-fundaments, and countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 139 publications
1
31
0
Order By: Relevance
“…At the same time, the TFA considers the global consequences of negative externalities. The environmental Kuznets curve (EKC) has been the focus of much academic attention because of concerns about the negative effects that rising prosperity has on the environment see [1][2][3]. Kuznets [4] first presented the EKC hypothesis, positing that income inequality would increase initially but decrease as the economy grew.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the TFA considers the global consequences of negative externalities. The environmental Kuznets curve (EKC) has been the focus of much academic attention because of concerns about the negative effects that rising prosperity has on the environment see [1][2][3]. Kuznets [4] first presented the EKC hypothesis, positing that income inequality would increase initially but decrease as the economy grew.…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-established notion in the body of academic research that the industrial revolution is to blame for the buildup of greenhouse gases and, in the long run, plays a harmful role in the deterioration of the status of the environment. In the last several decades, studies in empirical studies have been attempting to find out the fundamental reasons for environmental deterioration; nevertheless, [1][2][3][4][5][6] there has not been able to be reached an agreement about the accountable variables. In addition, the existing body of research suggests that an increasing number of researchers have identified a group of macro fundamentals directly or indirectly associated with environmental degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the academic study provide unequivocal evidence in favor of the premise that technological innovation plays a significant role in both the competitiveness of industries and the development of nations (Tidd and Bessant, 2020;JinRu and Qamruzzaman, 2022;Zhao and Qamruzzaman, 2022). Some businesses are more innovative in their use of technology than others, and the factors that influence their inventiveness are of interest to management academics, managers in practice, innovation consultants, and policymakers in the technology field.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 88%